Effects of parabens on antioxidant system and oxidative damages in Nile tilapia (Oreochromis niloticus) - Silva, Daniele C.; Serrano, Lenard; Oliveira, Thiessa M.A.; Mansano, Adrislaine S.; Almeida, Eduardo A. [UNESP]; Vieira, Eny M. (Elsevier, 2018)
In this study, effects of parabens on antioxidant defenses and oxidative damages in gills and liver of Nile tilapia (Oreochromis niloticus) were evaluated. Adult Nile tilapia were exposed to methyl, ethyl, propyl, butyl and benzylparaben and a mixture of methyl and propylparaben for 6 and 12 days. The biomarkers analyzed were superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), total glutathione (GSH-t) and lipid peroxidation measured by malondialdehyde (MDA) content. Results indicated that exposure to parabens caused biochemical changes in gill and liver cells, which in turn modulated enzymatic and non-enzymatic antioxidants in Nile tilapia. SOD, GPx and GR activity significantly increased in gills and liver after exposure to most parabens. CAT activity had little (liver) or no alteration (gills) in this fish species after treatment with parabens. GSH-t content in liver decreased after 6 days of exposure to parabens, but after 12 days, GSH-t levels increased in liver in all treatments, indicating an antioxidant adaptation to exposure to sublethal doses of parabens. Regarding the MDA levels, no alterations were observed in gills compared to control and in liver the MDA content was reduced after 12d of exposure to ethylparaben, butylparaben and paraben mixture, indicating no lipid peroxidation in the analyzed tissues. Our results demonstrate parabens-induced adaptive responses in fish, which were important in the protection against oxidative damages.
Keywords: Antioxidant enzymes; Biomarkers; Fish; Oxidative stress; Paraben